Development of cost effective PLC training kit by using arduino platform (PLCDUINO) - Mohd Samsudin, Mohd Safit (2015)
Programmable Logic Controller (PLC) is an industry demand practical based subject which required hands on experience of programming and hardware wiring. Because of such nature, the course is usually delivered with the help of PLC training kit. The kit generally consists of PLC incorporating switches as an input and lamps as an output. However cost of owning a PLC training kit is quite expensive and the PLC itself dominates the total cost. In this project, a solution for catering such an issue is proposed by introducing PLCduino training kit. Basically the systems use standard PLC Ladder diagram and implement it under cheap Arduino microcontroller platform. The Ladder instruction set is automatically converted to the Arduino language with the usage of LDuino software, while the PLC voltage requirement is fulfilled by using couple of relay boards. The system is expected to deliver the same performance of standard PLC system with more than 50 percent cheaper in price.